Are Patients who are Diagnosed with Hypertension or Diabetes more likely to Receive the COVID-19 Booster? Data from PR-CEAL’s Community Survey Tool - Vidal-Vega, Valeria V.; Berríos-Ortiz, Hérmilis; Canales-Birriel, Karelys; Colón-López, Vivian (Puerto Rico Health Sciences Journal, 2024)
Objective: Evaluate the relationship between diabetes and hypertension and COVID-19 booster uptake. Methods: Members of the Community Outreach Group of the Puerto Rico Community Engagement Alliance Against COVID-19 Disparities (PR-CEAL) administered a survey at 229 community events between November 2021 and May 2023. Information on 2,145 participants’ sociodemographic information and chronic disease diagnoses was gathered. Characteristics distributions were described using frequency and percentages. The associations between demographic factors and booster uptake were assessed using chi-squared analysis for categorical variables. Multivariate logistic regression models were used to estimate odds ratios (OR) with 95% confidence intervals (CI), adjusting for age, sex, education, and medical insurance, to investigate the relationship between hypertension and diabetes and booster uptake. Results: Participants’ mean age was 43.8 years. Most (80%) were women and had received a COVID-19 booster (84%). A high prevalence of hypertension (43%) and diabetes (33%) was observed in this study sample. Bivariate analyses showed a statistically significant association between receiving the booster and having hypertension or diabetes (p<0.05). Adjusted multivariate analysis showed that participants with diabetes were 3% more likely to have the booster than those without diabetes (OR=1.03, 95% CI: (1.01-1.05), p<0.05). No significant association was found between hypertension and booster uptake in the adjusted multivariate analysis (OR=1.01, 95% CI: (0.99-1.03), p=0.13). Conclusion: Insights from this study can inform future vaccination campaigns through improved awareness and prevention strategies by targeting vulnerable populations in Puerto Rico.